A comprehensive update on the morphology and distribution of the invasive scaffold-web spider Eidmannella pallida (Araneae, Nesticidae) with a focus on new records from Italy - Nardi, Davide; Pantini, Paolo; Rizzo, Pierluigi; Trespidi, Giacomo; Turetta, Alessandra; Barbieri, Giacomo; Ballarin, Francesco (Zootaxa, 2023)
Updated non-native distributional data of the invasive spider Eidmannella pallida (Emerton, 1875), Nesticidae, are herein summarized together with the morphological characters of the species. We report all the known localities from the literature. Furthermore, we present and discuss recent findings for the Italian peninsula. In particular, the species has been consistently found in vineyards and annual crop fields in North Italy and in olive groves in South Italy. We include a redescription of the species, and detailed illustrations of the diagnostic characters of both males and females, based on stereomicroscope and SEM images. The spreading potential of the species and its possible impacts on local communities are discussed. Our data suggest that E. pallida has high invasiveness potential and several new findings in non-native areas were recorded in the last years. We found that E. pallida can establish permanent populations in crop-dominated landscapes and has a tendency to exploit vulnerable ecosystems such as the subterranean environment. We thus recommend new and more comprehensive studies on this species to investigate in deeper detail its phylogeny, ecology, and micro-habitat preferences. A high effort should be placed to assess the potential negative effects of E. pallida on the endemic fauna in invaded areas, especially in caves.